Effect of Oral Diazepam on Newborn as Premedicant: a Study of 100 Patients Undergone Caesarian Section (TAJ: Journal of Teachers Association, 2011)
Oral diazepam as premedicant is useful to keep the patient haemodynamically stable causing no harm to the baby. In obstetrics, benzodiazepines may be used as sedative, narcotics adjuvant, anticonvulsants and premedicants prior to Caesarian section. One hundred full-term pregnant women of ASA grade I and II were enrolled in this study. The study sample was divided into two groups. No premedication was given in group A. In group B, diazepam premedication, 0.2 rng/kg body weight orally was given 90 minutes before operation with the aim to see the effectiveness of diazepam on APGAR score as oral premedication. In both the group A and B there was no significant difference of APGAR score.   DOI: http://dx.doi.org/10.3329/taj.v14i2.8387 TAJ 2001; 14(2): 61-64